2020
DOI: 10.1002/ppul.24578
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of elevated FeNO and airway hyperresponsiveness in nonasthmatic adolescents

Abstract: Objectives The aim of this study was to investigate airway responsiveness and eosinophil and neutrophil inflammatory markers in clinically confirmed nonasthmatic adolescents with elevated fractional exhaled nitric oxide (FeNO), a marker of type‐2 inflammation in the airways. Methodology A total of 959 subjects from a general population, aged 12 to 15 years, answered a standardised questionnaire and underwent FeNO measurements at a screening visit at school. Adolescents without asthma, who had elevated FeNO (Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(80 reference statements)
1
4
0
1
Order By: Relevance
“…In addition, as set out in tables 3 and 4, RDR was found to be only associated with CANO rather than FeNO 50 in non-asthmatic subacute cough. Although FeNO 50 has been validated to be associated with airway responsiveness [25,26], several studies suggested that CANO might be more relevant to airway responsiveness [27,28]. Therefore, it is comprehensible that only CANO, not FeNO 50 , was significantly associated with RDR, which was also consistent with our former conclusion that CANO showed a stronger correlation with spirometric parameters than FENO 50 in asthmatic and non-asthmatic subacute cough.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, as set out in tables 3 and 4, RDR was found to be only associated with CANO rather than FeNO 50 in non-asthmatic subacute cough. Although FeNO 50 has been validated to be associated with airway responsiveness [25,26], several studies suggested that CANO might be more relevant to airway responsiveness [27,28]. Therefore, it is comprehensible that only CANO, not FeNO 50 , was significantly associated with RDR, which was also consistent with our former conclusion that CANO showed a stronger correlation with spirometric parameters than FENO 50 in asthmatic and non-asthmatic subacute cough.…”
Section: Discussionsupporting
confidence: 87%
“…Дані 9 досліджень показали, що, хоча рівні FeNO у дітей у віці 0-4 років корелюють з прогностичним індексом астми та візингом, однак, очевидно, недостатньо доказів, щоб визначити, чи результати FeNO у віці 0-4 років можуть надійно передбачити майбутній діагноз астми [8,9]. Також є дані що у багатьох підлітків без наявної клінічної картини астми відзначається підвищення рівня FeNO, що вказує на наявну гіперчутливість бронхів, пряму кореляцію з рівнем еозинофілів крові та може бути предиктором розвитку БА у майбутньому [2].…”
Section: Asthma and Allergyunclassified
“…14 FENO has also been found to correspond well to elevated levels of blood eosinophils, often correlated to allergic inflammation. 22 Both peanut allergic individuals with and without asthma 23 have been found to express high levels of FENO even though peanut is primarily a food and not inhalant allergen. 23,24 Johnson et al have reported that asthmatic patients aged 10-35 years, with a sensitization to peanut allergen molecules Ara h 1, h 2 and h 3 or the hazelnut storage proteins Cor a 9 and Cor a 14, were found to express higher levels of FENO than individuals without peanut sensitization, 24 especially in the youngest age group.…”
Section: Inflammatory Biomarkers and Systemic Inflammationmentioning
confidence: 99%
“…FENO is driven by the activation of the Th2 pathway 18 and elevated levels are often found in patients with untreated type 2 inflammation in bronchi and bronchioles, comorbid nasal polyposis, airborne allergy and in patients with an airborne allergy such as to furry animals, house dust mites and pollen 14,19–21 and food allergens 14 . FENO has also been found to correspond well to elevated levels of blood eosinophils, often correlated to allergic inflammation 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation